Long-term survival in advanced pulmonary large-cell neuroendocrine carcinoma after multi-line immunochemotherapy and anti-angiogenic therapy: a case report - Wang, Hongming; Li, Shiyan; Liu, Xiaoyang; Zhang, Yan; Zheng, Jiang; Du, Yangfeng; Xiao, Zemin; Wang, Nuoni; Wu, Zhijun (Frontiers in Immunology, 2025)
BackgroundPulmonary large-cell neuroendocrine carcinoma (PLCNEC) is a rare and highly aggressive subtype of lung cancer with neuroendocrine features, typically diagnosed at an advanced stage. Its clinical presentation and treatment response resemble those of small cell lung cancer, whereas its histological characteristics are more similar to those of non-small cell lung cancer. The rarity and heterogeneity of PLCNEC have impeded the development of standardized treatment protocols. Conventional approaches such as surgery, chemotherapy, and radiotherapy alone have yielded poor outcomes, underscoring the need for more effective therapeutic strategies.Case descriptionThis report presents the case of a 45-year-old Chinese woman with advanced PLCNEC who received first-line treatment with a four-drug regimen consisting of etoposide, cisplatin, camrelizumab, and endostar. This was followed by maintenance therapy with camrelizumab and endostar, local palliative radiotherapy, re-administration of etoposide and cisplatin, and hepatic artery interventional embolization. Notably, her progression-free survival (PFS) after first-line therapy (i.e., PFS1) reached 2 years. Second-line therapy with atezolizumab, bevacizumab, and docetaxel achieved a PFS2 of 1 year. Third-line treatment maintained atezolizumab and introduced the anti-angiogenic agent anlotinib and chemotherapeutic agent pemetrexed, resulting in a PFS3 of 6 months. The patient tolerated all treatments well, with no grade 3 or 4 adverse events observed, and achieved a total overall survival of 47 months.ConclusionsThis case illustrates the potential for long-term survival in advanced PLCNEC through intensive, multi-line combination therapies. The favorable outcome observed in this patient supports further investigation of such combination strategies in clinical studies.